2019
DOI: 10.1097/hjh.0000000000001835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additional vasodilatory or nonvasodilatory treatment on renal function, vascular resistance and oxygenation in chronic kidney disease

Abstract: Long-term intensified vasodilation treatment reduced peripheral and RVR, but this was not associated with improvement of R2* or protection against loss of kidney function in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…Regardless of considerably increased BP before transplantation, the recipients did not have elevated forearm vascular resistance, either at rest or during maximal vasodilation. This finding is in accordance with another recent study from our department 31 but differs from findings in persons with untreated essential hypertension who display elevated Rrest and Rmin due to structural resistance artery remodeling. 32,33 This discrepancy may be explained by ongoing extensive vasodilating antihypertensive therapy among the recipients in terms of renin-angiotensin and calcium channel blockade inhibiting arterial inward structural narrowing.…”
Section: Renal Transplant Recipientssupporting
confidence: 91%
“…Regardless of considerably increased BP before transplantation, the recipients did not have elevated forearm vascular resistance, either at rest or during maximal vasodilation. This finding is in accordance with another recent study from our department 31 but differs from findings in persons with untreated essential hypertension who display elevated Rrest and Rmin due to structural resistance artery remodeling. 32,33 This discrepancy may be explained by ongoing extensive vasodilating antihypertensive therapy among the recipients in terms of renin-angiotensin and calcium channel blockade inhibiting arterial inward structural narrowing.…”
Section: Renal Transplant Recipientssupporting
confidence: 91%
“…Last, PC-MRI was used to measure renal arterial blood flow and calculate renal vascular resistance in a study comparing vasodilatory and non-vasodilatory antihypertensive treatment in patients with CKD. After 18-month follow-up, RABF increased significantly in both groups, but the change did not differ between groups [60].…”
Section: Chronic Kidney Diseasementioning
confidence: 74%
“…24 With regard to effects of common medications, treatment with amlodipine (a dihydropyridine calcium-channel blocker promoting coronary and systemic vasodilation) and/or renin-angiotensin-system inhibitors significantly decreased forearm resistance measured by VOP compared with metoprolol (a cardioselective competitive beta-1 adrenergic receptor antagonist) in patients with advanced CKD. 25 Similar results were observed in another randomized study using low dose of the mineralocorticoid receptor antagonist spironolactone versus placebo in haemodialysis patients without heart failure. 26…”
Section: Venous Occlusion Plethysmographysupporting
confidence: 76%
“… 23 In another prospective study with a follow‐up of 92 ± 36 months including 500 treatment‐naïve uncomplicated hypertensive patients, Perticone et al demonstrated that endothelium‐dependent vasodilation of the forearm—assessed by acetylcholine‐stimulated vasodilation during VOP—was associated with renal function decline after adjustment for other traditional cardiovascular risk factors 24 . With regard to effects of common medications, treatment with amlodipine (a dihydropyridine calcium‐channel blocker promoting coronary and systemic vasodilation) and/or renin‐angiotensin‐system inhibitors significantly decreased forearm resistance measured by VOP compared with metoprolol (a cardioselective competitive beta‐1 adrenergic receptor antagonist) in patients with advanced CKD 25 . Similar results were observed in another randomized study using low dose of the mineralocorticoid receptor antagonist spironolactone versus placebo in haemodialysis patients without heart failure 26 …”
Section: Techniques For Assessment Of Endothelial Dysfunction In Ckdmentioning
confidence: 99%